Synthesis and Spectral Characterization of Hexahydroxy Tris-Cyclophosphazene Hexaacrylate - Rani, Illa; Jadon, S.P.S. (Asian Journal of Chemistry, 2010)
Acrylic acid was mixed with hexahydroxycyclo phosphazene [NP(OH)2)]3 in equimolar ration in DMF followed by conc. H2SO4 and refluxed for 6 h. The product, obtained, was analyzed, quantitatively, as well as, mass, IR and UV spectrometrically and formulated as [P3N3(OH)2–C(OOC–CH=CH)2]3 as ionic polymer (trimer), having (CH=CH–COO)–P3N3(OH)2 units.